Marketing in the Sharing Economy. (September 2019) - Eckhardt, Giana M.; Houston, Mark B.; Jiang, Baojun; Lamberton, Cait; Rindfleisch, Aric; Zervas, Georgios
The last decade has seen the emergence of the sharing economy as well as the rise of a diverse array of research on this topic both inside and outside the marketing discipline. However, the sharing economy's implications for marketing thought and practice remain unclear. This article defines the sharing economy as a technologically enabled socioeconomic system with five key characteristics (i.e., temporary access, transfer of economic value, platform mediation, expanded consumer role, and crowdsourced supply). It also examines the sharing economy's impact on marketing's traditional beliefs and practices in terms of how it challenges three key foundations of marketing: institutions (e.g., consumers, firms and channels, regulators), processes (e.g., innovation, branding, customer experience, value appropriation), and value creation (e.g., value for consumers, value for firms, value for society) and offers future research directions designed to push the boundaries of marketing thought. The article concludes with a set of forward-looking guideposts that highlight the implications of the sharing economy's paradoxes, maturation, and technological development for marketing research. Collectively, this article aims to help marketing scholars not only keep pace with the sharing economy but also shape its future direction.